Body‐worn cameras as a potential source of depolicing: testing for camera‐induced passivity - Wallace, Danielle Marie (Criminology, 2018)
Contentious debate is currently taking place regarding the extent to which public scrutiny of the police post‐Ferguson has led to depolicing or to a decrease in proactive police work. Advocates of the “Ferguson effect” claim the decline in proactive policing increased violent crime and assaults on the police. Although police body‐worn cameras (BWCs) are touted as a police reform that can generate numerous benefits, they also represent a form of internal and public surveillance on the police. The surveillance aspect of BWCs suggests that BWCs may generate depolicing through camera‐induced passivity. We test this question with data from a randomized controlled trial of BWCs in Spokane (WA) by assessing the impact of BWCs on four measures: officer‐initiated calls, arrests, response time, and time on scene. We employ hierarchical linear and cross‐classified models to test for between‐ and within‐group differences in outcomes before and after the randomized BWC rollout. Our results demonstrate no evidence of statistically significant camera‐induced passivity across any of the four outcomes. In fact, self‐initiated calls increased for officers assigned to treatment during the RCT. We discuss the theoretical and policy implications of the findings for the ongoing dialogue in policing.